2015
DOI: 10.1371/journal.pone.0122496
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and Obesity as Potential Risk Factors of Sudden Sensorineural Hearing Loss

Abstract: ObjectivesThe objective of our study was to establish whether increased lipid profiles and obesity affect the prevalence and prognosis of sudden sensorineural hearing loss (SSNHL).MethodsThis was a case-controlled study with a longitudinal design. According to our criteria, 324 patients with SSNHL were included in this study. To manage potential covariates, 972 subjects with normal hearing from the Korean National Health and Nutrition Examination Survey were matched as control group according to their propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 25 publications
(38 reference statements)
2
70
0
Order By: Relevance
“…In the present study we did not find higher levels of lipids in ISSHL patients. Similar results were reported by Chang et al [30], while other authors have reported a correlation between ISSHL and hyperlipidemia [31,32]. The role of hyperlipidemia needs therefore to be further investigated.…”
Section: Plos Onesupporting
confidence: 85%
“…In the present study we did not find higher levels of lipids in ISSHL patients. Similar results were reported by Chang et al [30], while other authors have reported a correlation between ISSHL and hyperlipidemia [31,32]. The role of hyperlipidemia needs therefore to be further investigated.…”
Section: Plos Onesupporting
confidence: 85%
“…27 Lipid metabolic disorders may contribute to cochlear ischemia due to increased blood viscosity and increased thickness of the endothelium of the terminal blood vessels through several mechanisms, including the formation of atheromatous plaques, endothelial dysfunction, and vascular inflamation. 8,[28][29][30] In this regard, a study 31 including 94 patients with SSNHL showed a significant negative correlation between hearing recovery and total cholesterol levels. Diabetes may also induce cochlear microangiopathy, resulting in SSNHL and reducing the rate of recovery from this condition.…”
Section: Discussionmentioning
confidence: 95%
“…ILH may cause sudden hearing deterioration with vertigo in a patient on anticoagulant therapy or with a hematological disease; the prevalence has been reported as 0.3–6.25% in patients with SSNHL [ 7 , 22 , 23 ]. In our series of 200 3-T MRI scans, seven (3.6%) patients showed ILH on MRI, which was the second-most common finding after tumors invading the IAC (10 patients, 5.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact etiology of SSNHL is still debated (such that it is classified as idiopathic), viral infections, immunological diseases, and impairment of the vascular microcirculation have been suggested as possible causes [ 2 , 4 6 ]. Recently, studies have shown that abnormal serum lipid levels [ 7 , 8 ] and thyroid dysfunction were also significantly associated with the occurrence and prognosis of SSNHL [ 9 ]. However, no laboratory test can accurately predict the prognosis of SSNHL and no treatment modality has been established based on medical evidence, despite biological plausibility.…”
Section: Introductionmentioning
confidence: 99%